Billy Lynn's long halftime walk [videorecording (DVD)] - Alwyn, Joe; Stewart, Kristen, 1990-; Diesel, Vin; Fountain, Ben (Sony Pictures Home Entertainment, 2017)
Nineteen-year-old Billy Lynn is brought home for a victory tour after a harrowing Iraq battle. Through flashbacks the film shows what really happened to his squad, contrasting the realities of war with America's perceptions.